Polypoidal choroidal vasculopathy in a case of retinitis pigmentosa, successfully treated with intravitreal aflibercept - Takahashi, Nana (Am J Ophthalmol Case Rep, 2021)
PURPOSE: Polypoidal choroidal vasculopathy (PCV) is a subtype of age-related macular degeneration that is seen frequently in Asians. Nevertheless, it is rare for this condition to be combined with retinitis pigmentosa (RP). The purpose of this paper is to present findings from this rare combination in a Japanese patient, and to describe its successful treatment with intravitreal aflibercept (IVA). OBSERVATIONS: The patient was a 71-year-old Japanese woman with RP (diagnosed at the age of 30) and PCV. She noticed a decrease in vision in her right eye 6 months previously. Decimal best-corrected visual acuity (BCVA) was 0.05 in her right eye. Optical coherence tomography and indocyanine green angiography (IA) revealed serous retinal detachment (SRD) and PCV in her right eye. The SRD was initially resolved after 3 monthly treatments with IVA, but recurrences began 5 months later, requiring four more treatments with IVA, performed about every 4 months within the next 12 months, for successful resolution. There were no recurrences of PCV in 7 more months of follow-up, as confirmed with IA at the final appointment. Final decimal BCVA in the right eye improved to 0.15. Furthermore, macular retinal sensitivity, measured with microperimetry, increased after the treatment, and RP-related visual field narrowing, determined by Goldmann perimetry, did not progress throughout follow up of 26 months. CONCLUSION: More than 2 years of follow up showed that IVA may be effective for treating PCV, even in RP patients, and can increase central visual function without causing progression of RP-related visual field narrowing.